2022
DOI: 10.3390/healthcare10020275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Actual Use Behavior of Healthcare Wearable Devices on Quality of Life: A Cross-Sectional Survey of People with Dementia and Their Caregivers in Ghana

Abstract: The increasing prevalence of dementia has necessitated the introduction and use of healthcare wearable devices to augment the healthcare services delivered to people with dementia (PWDs). Unfortunately, evidence on user feedback and the real impact of the actual use of these devices on the quality of life of PWDs has not been fully explored, especially in the context of developing countries. This study, therefore, seeks to evaluate the impact of actual use behavior (AUB) of healthcare wearable devices on the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…From 50 of the included studies, the following were used to promote autonomy: patient monitoring [25], [38], [39], [46], [50], [51], [61], [93]–[95], [100], [101], [103], [105]–[108], [111], [120]–[123], [125], [132], [137], [141], care support [53], [95] and digital therapeutics [21], [22], [25], [30], [32], [33], [38], [39], [49]–[51], [53], [56], [60], [61], [64], [70], [80]–[82], [86], [91], [93]–[95], [100], [104], [105], [107], [109]–[111], [114], [123], [125], [131], [138], [141]. Resilience was also mentioned as a significant factor contributing to enhanced autonomy [41], [62], [129], [130].…”
Section: Resultsmentioning
confidence: 99%
“…From 50 of the included studies, the following were used to promote autonomy: patient monitoring [25], [38], [39], [46], [50], [51], [61], [93]–[95], [100], [101], [103], [105]–[108], [111], [120]–[123], [125], [132], [137], [141], care support [53], [95] and digital therapeutics [21], [22], [25], [30], [32], [33], [38], [39], [49]–[51], [53], [56], [60], [61], [64], [70], [80]–[82], [86], [91], [93]–[95], [100], [104], [105], [107], [109]–[111], [114], [123], [125], [131], [138], [141]. Resilience was also mentioned as a significant factor contributing to enhanced autonomy [41], [62], [129], [130].…”
Section: Resultsmentioning
confidence: 99%
“…The study, using an inductive, qualitative design and semi-structured interviews, found that some healthcare workers seemed to be afraid and distressed by new technology and at times unintentionally tampered with hardware without knowing what they were doing or how to fix it [40]. Technology anxiety can be reduced and addressed by deploying specific strategies for dialog with both the PwD and their caregivers (formal and informal) [40,63].…”
Section: Technology Anxietymentioning
confidence: 99%
“…For example, downloading a pedometer app could help enhance their PA. Moreover, facilitating the use of wearables and making them less noticeable and user-friendly, while providing appropriate operating instructions, could help reduce anxiety about technology use [61,62]. Today, there are different types of products (smartwatches, fitness trackers, smart clothes, implantable gadgets, head-mounted displays, etc) from various manufacturers (Xiaomi, Huawei, Polar, Samsung, Apple, Garmin Ltd, Withings, and Fitbit just to name a few) that are available in the market; the variety of options can be daunting for informal caregivers when making decisions about which wearable device to adopt and use [62,63].…”
Section: Principal Findings and Implications For Policy And Practicementioning
confidence: 99%